(untitled) (Connessioni remote. Artivismo_Teatro_Tecnologia, 2024)
This paper focuses on the theme of world-building applied to a series of contemporary sound projects, proposing a multidisciplinary approach aimed at outlining their characteristics in relation to the interaction with the listener. The text explores the speculative dimension of these projects, highlighting how, in addition to representing reality, it is also questioned, fostering a critical analysis of contemporary political and social issues. The article begins with Alice Bucknell’s New Worlds exhibition and Simon Reynolds’ The Rise of Conceptronica, which provide the theoretical context to understand the growing role of sound-based world-building. By applying Azuma’s “database” model, the structure of these projects will be explored, with particular attention given to the agency of sound, which plays a crucial role in transforming bodies and spaces. Furthermore, sonic fiction and speculative design will be analyzed as practices within these projects, subverting traditional narrative structures and acting as key tools to explore contemporary themes such as control, resistance, and inclusion. These works offer new ways of conceiving the future, proposing alternatives to dominant visions and opening spaces for critical reflection on reality and its potential transformations.